2018
DOI: 10.1021/acs.jpcc.7b09363
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Trends from Metal Substitution in Bimetallic Mo-Based Phosphides for Hydrodeoxygenation and Hydrogenation Reactions

Abstract: Bimetallic phosphides are promising materials for biomass valorization, yet many metal combinations are understudied as catalysts and require further analysis to realize their superior properties. Herein, we provide the synthesis, characterization, and catalytic performance of a variety of period 4 and 5 solid solutions of molybdenum-based bimetallic phosphides (MMoP, M = Fe, Co, Ni, Ru). From the results, the charge sharing between the metals and phosphorus control the relative oxidation of Mo and reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 68 publications
3
36
0
Order By: Relevance
“…Overall, the presence of P atoms alters the catalytic properties of Ru(0001) likely as a consequence of charge transfer from Ru to P atoms on the surface, which reduces the extent of electron exchange between metal atoms and the adsorbates. 71 These resulting changes in the product distribution show that these differences in the electronic structure of Ru apparently increase barriers and reduce reactivity for C−O, C−C, and C−H bond ruptures. However, these results cannot exclude the possibility that changes in the Ru−Ru coordination and bond lengths caused by the presence of P atoms modify surface chemistry by ensemble effects.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the presence of P atoms alters the catalytic properties of Ru(0001) likely as a consequence of charge transfer from Ru to P atoms on the surface, which reduces the extent of electron exchange between metal atoms and the adsorbates. 71 These resulting changes in the product distribution show that these differences in the electronic structure of Ru apparently increase barriers and reduce reactivity for C−O, C−C, and C−H bond ruptures. However, these results cannot exclude the possibility that changes in the Ru−Ru coordination and bond lengths caused by the presence of P atoms modify surface chemistry by ensemble effects.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, TPR of C 6 H 6 also suggests that P atoms significantly decrease the C 6 H 6 binding energy and extent of C 6 H 6 decomposition in comparison to Ru(0001), which can promote C 6 H 6 desorption over decomposition and lead to decreased coking during TPR of C 6 H 10 (Figure S3). While these results indicate that the presence of P atoms within the P 0.4 -Ru­(0001) surface withdraw charge from Ru atoms, consistent with XPS of related TMP nanoparticles, Muetterties et al demonstrated that adsorption of trimethyl phosphine could liberate reactive intermediates of dehydrogenation reactions from Ni , and Pt surfaces. To further understand the dehydrogenation selectivity and intrinsic barriers, we probe the mechanism of C 6 H 10 dehydrogenation over Ru(0001) and P 0.4 -Ru­(0001).…”
Section: Resultsmentioning
confidence: 68%
“…Previously reported Bader charge analysis and differences among core-electron binding energies detected by X-ray photoelectron spectroscopy (XPS) and X-ray absorption near-edge structure demonstrate that charge transfers from transition metals to P in TMP, which results in electronic modifications of the transitions metals. These electronic modifications decrease the binding energy of the dehydrogenation product and facilitate the desorption of olefins over further dehydrogenation. In addition, these electronic changes can modify the binding modes and configuration of surface intermediates caused by interactions with cationic metal and anionic P atoms exposed at surfaces. ,, …”
Section: Introductionmentioning
confidence: 99%
“…P-Containing catalysts, also known as metal phosphides, are known particularly for hydrodesulfurization, hydrodeoxygenation, and hydrogenation reactions. [8][9][10][11][12][13] Additionally, many metal phosphides are made from earth abundant metals, such as Ni, Co, Mo, and Fe, and have been identified as promising alternatives to noble metal based catalysts for many industrially relevant reactions. 14,15 For light alkane dehydrogenation reactions, P promotion of Ni results in improved selectivity to the desired alkene as well as improved stability over monometallic Ni nanoparticles.…”
Section: Introductionmentioning
confidence: 99%